Nematodes from the Strait of Magellan and the Beagle Channel (Chile): the genera Cervonema and Laimella (Comesomatidae, Nematoda) - Chen, G.; Vincx, M. (Hydrobiologia, 2000)
Locality: Strait of Magellan, Beagle Channel, Chile; Cabinet:
Locality: Strait of Magellan, Beagle Channel, Chile; Cabinet: NeMys doc_id: 9648